United States monetary policy, recent thinking and experience: Hearings before the Subcommittee on Economic Stabilization of the Joint Committee on the Economic Report, Congress of the United States, Eighty-third Congress, second session, pursuant to sec. 5(a) of Public law 304, 79th Congress. December 6 and 7, 1954 - United States (Washington : U.S. Govt. Print. Off., 1954)
This book contains the report of United States. Congress. Joint Economic Committee. Subcommittee on Economic Stabilization meeting on December 6, 1954.
Ralph E. Flanders, chairman of subcommittee.
usc 25/07/2017
Loans
Keywords: Currency question; United States